Modern Industrial Robotics Industry - Sotnik, S.; Lyashenko, V. (International Journal of Academic Engineering Research, 2022)
The purpose of article is to consider possibilities for use of industrial robots in modern production, task of study is to review current state of their application. The considered "novelties" of industrial robots from global trend manufacturers: powerful robot M-1000iA and small robot LR-10iA/10 from Fanuc; Yaskawa GP 215; ready2_spray from KUKA and short comparison of robots basic capabilities these three companies is provided. The paper presents extended classification of PR. In course of analysis in modern IR field, main trends in development of industrial robotics are highlighted.
Keywords: modern; industrial robotics